Immunological Aspects of Recombinant Factor Vila (rFVIIa) in Clinical Use - Nicolaisen, Else Marie; Hansen, Lisbeth Lyng; Poulsen, Fritz; Glazer, Steven; Hedner, Ulla (Thrombosis and Haemostasis, 1996)
Patients, receiving rFVIIa for treatment of bleeding disorders, have been followed for specific antibody formation. No antibodies against FVII were demonstrated in 170 patients, with hemophilia, or with acquired inhibitors to clotting factors. Of 6 FVII-deficient patients, one overdosed patient developed antibodies to human FVII. There was no indication of de novo formation of antibodies to potential contaminating foreign protein, which could be correlated to the rFVIIa treatment. Except for the FVII-deficient population, which may represent a risk group, rFVIIa appears to be immunologically safe for use in patient groups with bleeding disorders, including hemophilia A and B patients.